Tinjauan Hukum Islam terhadap Akad Sewa Menyewa Ruko Tempat Jualan di Desa Sungai Rengas Kecamatan Maro Sebo Ulu Kabupaten Batanghari - Harisman Harisman; Mashudi Hariyanto; Musaddad Al Basry (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
A shophouse rental in Sungai Rengas Village is suspected of being subject to fraud, one of which is related to unilateral price changes. The price determined at the beginning of the agreement was changed midway by the shophouse owner. The tenant who rented the additional shophouse as a game room suddenly experienced a unilateral price change. The price that had been determined at the beginning of the agreement, which was to be available once a month and the amount was determined at the beginning, but suddenly the shophouse owner changed it. The party renting the additional shophouse as a game room was ordered to pay all electricity to the tenant, which was initially covered by the shophouse owner. However, midway through the agreement, the electricity payment suddenly changed, all payments were borne by the party renting the additional shophouse as a game room, and the electricity payment had to be allowed once a week. The type of research in this study is empirical, which in other words is a type of sociological legal research and can also be called field research, namely studying the applicable legal provisions and what happens in reality in society. Based on the research results that the price changes that occurred to the tenant who added a field for the game area are not in accordance with Islamic law, because it violates one of the valid conditions of ijarah and is also not in accordance with the legal basis for determining prices. According to Islamic law, ijarah is a binding contract (al-'aqd aL-biasa), is a contract where if all the pillars and conditions have been fulfilled, then the contract is fully binding and each party cannot cancel it without the consent of the other party, the same as the rental contract and debt, both parties have agreed and have fulfilled the pillars and conditions of the ijarah contract immediately both are bound to each other. As in the case of not returning the rent, the market party.